2017
DOI: 10.1007/s00415-017-8648-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of pain in people with hereditary neuropathy with liability to pressure palsy

Abstract: Hereditary neuropathy with liability to pressure palsy (HNPP) has historically been considered a pain-free condition, though some people with HNPP also complain of pain. This study characterised persistent pain in people with HNPP. Participants provided cross-sectional demographic data, information on the presence of neurological and persistent pain symptoms, and the degree to which these interfered with daily life. The painDETECT and Central Sensitization Inventory questionnaires were used to indicate potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…A 40-point cut-off score of CSI part A was recommended to classify the presence of CSS in patients with chronic pain 6 , 8 . Many clinical studies have since reported the rates of a CSI score ≥ 40 in patients with CSS-related diseases: 11.0% in 290 orthopedic patients with musculoskeletal pain, including the neck, shoulders, hips, knees, or ankles 9 , 13% in 238 patients with low back pain 10 , 34.9% in 66 patients with pelvic floor muscle tenderness 11 , 48.4% in 91 patients with osteoarthritis 12 , 68.2% in 763 patients with chronic spinal pain disorder 13 , and 84% in 32 patients with hereditary neuropathy 14 . These findings demonstrated that the prevalence of CSS varied in a CSS-related disease-dependent manner; however, data on the general population is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A 40-point cut-off score of CSI part A was recommended to classify the presence of CSS in patients with chronic pain 6 , 8 . Many clinical studies have since reported the rates of a CSI score ≥ 40 in patients with CSS-related diseases: 11.0% in 290 orthopedic patients with musculoskeletal pain, including the neck, shoulders, hips, knees, or ankles 9 , 13% in 238 patients with low back pain 10 , 34.9% in 66 patients with pelvic floor muscle tenderness 11 , 48.4% in 91 patients with osteoarthritis 12 , 68.2% in 763 patients with chronic spinal pain disorder 13 , and 84% in 32 patients with hereditary neuropathy 14 . These findings demonstrated that the prevalence of CSS varied in a CSS-related disease-dependent manner; however, data on the general population is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, half of the patients with HNPP suffered from neuropathic pain (52%), mainly burning in the lower limbs. In other cohorts of similar size, the pain rate varied between 16.6% and 74% of patients (13,14). There were no electrophysiological differences based on the presence/absence of pain in these series.…”
Section: Discussionmentioning
confidence: 51%
“…Pain in HNPP is an emerging concept, in both short and long-term. Regarding recent cohorts, 15 to 75% of HNPP patients suffer from chronic neuropathic pain (12)(13)(14). These patients may be erroneously considered as suffering from fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%
“…The 40-point cut-off score of CSI part A was recommended to classify the presence of CSS in patients with chronic pain 6,8 . Many clinical studies have since reported the rates of a CSI score ≥40 in patients with CSS-related diseases: 11.0% in 290 orthopedic patients with musculoskeletal pain, including the neck, shoulders, hips, knees, or ankles 9 , 13% in 238 patients with low back pain 10 , 34.9% in 66 patients with pelvic floor muscle tenderness 11 , 48.4% in 91 patients with osteoarthritis 12 , 68.2% in 763 patients with chronic spinal pain disorder 13 , and 84% in 32 patients with hereditary neuropathy 14 . These findings demonstrated that the prevalence of CSS varied in a CSS-related disease-dependent manner; however, data on the general population is lacking.…”
Section: Introductionmentioning
confidence: 99%